Towards a Medically Approved Technology for Large-Scale Stem Cell Banks: Tools and Method - Katsen-Globa, A.; Schulz, J.C.; Baunach, J.S.; Ehrhart, F.; Oh, Y.-J.; Schön, U.; Kofanova, O.; Beier, A.F.J.; Wiedemeier, S.; Metze, J.; Shirley, S.; Spitkovsky, D.; et al. (Проблемы криобиологии и криомедицины, 2008)
The importance, of the development of stem cell cryobanking has increased recently with an augmentation of stem cell research and its therapeutic applications. The development of therapies is, among other things, limited by high sensitivity of stem cells to freezingthawing procedures. Thus, new approaches are needed for preservation and related evaluation methods, as well as new technologies for long term storage of large numbers of stem cells. Here we present selected recent improvements of stem cell cryopreservation, e.g. for freezing of adherent human embryonic stem cells using gel-like matrices. We report the application and performance of novel microsystem-based cryosubstrates and devices and describe new evaluation methods and the results of a thermal stress cycle study. В настоящее время возросла важность развития криобанков стволовых клеток в связи с их расширенным изучением и терапевтическим применением. Однако, наряду с другими факторами, вышеуказанная терапия ограничена высокой чувствительностью стволовых клеток к процедурам замораживания-оттаивания. Необходимы как новые подходы к криоконсервированию и связанным с ним методам оценки, так и новые технологии для долгосрочного хранения большого количества стволовых клеток. В настоящей работе мы представляем некоторые улучшенные методы криоконсервирования стволовых клеток, например замораживание эмбриональных стволовых клеток человека с использованием гелеобразного матрикса. Мы представляем результаты применения разработанных на базе микросистемной техники новых криосубстратов и устройств, а также описываем новые методы оценки и результаты изучения циклов температурного стресса. Наразі зросла важливість розвитку кріобанків стовбурових клітин у зв’язку з їх розширеним вивченням і терапевтичним застосуванням. Але водночас з іншими факторами вищезгадана терапія обмежена високою чутливістю стовбурових клітин до процедур заморожування-відтавання. Необхідні як нові підходи до кріоконсервування та повязаних з ним методам оцінки, так і нові технології для довгострокового зберігання великої кількості стовбурових клітин. В цій роботі ми представляємо деякі покращені методи кріоконсервування стовбурових клітин, наприклад заморожування ембріональних стовбурових клітин людини з використанням гелеподібного матриксу. Ми представляємо результати застосування розроблених на базі мікросистемної техніки нових кріосубстратів та приладів, а також описуємо нові методи оцінки і результати вивчення циклів температурного стресу.